An evaluation of common breast cancer gene mutations in a population of Ashkenazi Jews. Issue 1 (January 1998) - Lalloo, F; Cochrane, S; Bulman, B; Varley, J; Elles, R; Howell, A; Evans, D G
Abstract : OBJECTIVES: In view of the recent reports of recurrent mutations in BRCA1 and BRCA2 in the Ashkenazi Jewish population, we have undertaken to assess the frequency of these mutations in this population attending for genetic counselling and risk assessment of familial breast cancer. DESIGN: Mutation screening for the 185delAG and the 5382insC mutations in BRCA1 and the 6174delT mutation in BRCA2 was performed on DNA samples from either subjects affected by breast or ovarian cancer or obligate gene carriers. The likelihood of the cancers being hereditary in each family was calculated. SUBJECTS: Blood samples were obtained from 26 affected subjects or obligate gene carriers from 23 Ashkenazi Jewish families, all with a history of either early onset breast or ovarian cancers, or multiple cases of breast or ovarian cancer. RESULTS: Twelve mutations have been identified in the 23 families (52%) of which eight (67%) were the 185delAG mutation, three (25%) were the 6174delT mutation, and one (8%) was the 5382insC mutation. While the majority of these mutations were identified in families with a greater than 50% probability of being hereditary under the CASH segregation model, three mutations were identified in families with a 35% or less probability. CONCLUSIONS: Genetic screening of the recurrent mutations in Ashkenazi Jewish families will lead to the availability of predictive testing in a reasonably large proportion, even if the family history of breast/ovarian cancer is not particularly strong. In our view it is possible to reassure high risk unaffected members of these families, if the screening is negative for these mutations, even if a sample from an affected member of the family is unavailable for previous screening.